2018
DOI: 10.1038/s41467-018-05852-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Wwox drives metastasis in triple-negative breast cancer by JAK2/STAT3 axis

Abstract: Loss of WW domain-containing oxidoreductase (Wwox) expression has been observed in breast cancer (BC). However, its regulatory effects are largely unknown, especially in triple-negative breast cancer (TNBC). Herein, gene expression profiling revealed that JAK/STAT3 pathway was one of the most differentially modulated pathways in basal-like BC cells. The lower expression of Wwox was significantly correlated with high activation of STAT3 in basal-like cells and TNBC tissues. Overexpression of Wwox markedly inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
88
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 64 publications
5
88
1
Order By: Relevance
“…The P65 pathway has been found to mediate the process of ischemic brain injury, hence a promising therapeutic target for ischemic stroke, and ikB as the master inhibitor of the P65 pathway, to have a degrading function during pathway activation (Hayden et al, 2008;Tu et al, 2014;Wang et al, 2017). A recent study has shown that linagliptin could suppress the expression of phosphorylated J A K 2 , p h o s p h o r y l a t e d S T A T 3 a n d P 6 5 t o c o n f e r neuroprotection (Marotta et al, 2011;Chang et al, 2018;Elbaz Eman et al, 2018). These results are similar to those which were found in the current study, which suggests the effects of inflammation reduction and neuroprotection.…”
Section: Discussionsupporting
confidence: 91%
“…The P65 pathway has been found to mediate the process of ischemic brain injury, hence a promising therapeutic target for ischemic stroke, and ikB as the master inhibitor of the P65 pathway, to have a degrading function during pathway activation (Hayden et al, 2008;Tu et al, 2014;Wang et al, 2017). A recent study has shown that linagliptin could suppress the expression of phosphorylated J A K 2 , p h o s p h o r y l a t e d S T A T 3 a n d P 6 5 t o c o n f e r neuroprotection (Marotta et al, 2011;Chang et al, 2018;Elbaz Eman et al, 2018). These results are similar to those which were found in the current study, which suggests the effects of inflammation reduction and neuroprotection.…”
Section: Discussionsupporting
confidence: 91%
“…Over the years it has been questioned whether CFS genes were or not genuine cancer gene targets or mere bystanders . Evidence from multiple studies has accumulated suggesting that indeed WWOX behaves as a low‐penetrance tumor suppressor with far more significant roles for affecting tumor progression rather than initiation in specific tumor types . Interestingly, loss of WWOX function has recently been associated with abnormalities in DNA damage repair (DDR), increased genomic instability, and resistance to chemoradiotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Evidence from multiple studies has accumulated suggesting that indeed WWOX behaves as a low-penetrance tumor suppressor with far more significant roles for affecting tumor progression rather than initiation in specific tumor types. [15][16][17][18][19] Interestingly, loss of WWOX function has recently been associated with abnormalities in DNA damage repair (DDR), increased genomic instability, and resistance to chemoradiotherapy. 20,21 In conjunction, the described observations place WWOX both as a target of and a contributor to genomic instability.…”
mentioning
confidence: 99%
“…Our data indicated that the CCD of STAT3 was essential for the interaction with ASRPS. Previous studies indicate that the CCD of STAT3 is essential for auto-phosphorylation (Ma et al, 2003; Zhang et al, 2000), and certain proteins could inhibit STAT3 activation by binding to STAT3 CCD domain (Chang et al, 2018; Mattagajasingh et al, 2012). Even K116, a STAT3 allosteric inhibitor, inhibited STAT3 phosphorylation at Tyr705 by binding to the CCD of STAT3 (Huang et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…TNBC is the most aggressive subtype of BC and is associated with worst prognosis and overall survival (OS; Son et al, 2019). It is characterized by high cell proliferation, poor cellular differentiation, and more frequent disease recurrence (Chang et al, 2018). Compared with non-TNBC, TNBC patients have poor prognosis, including higher nuclear grade, increased incidence of lung and brain metastases, and shorter recurrence-free interval.…”
Section: Introductionmentioning
confidence: 99%